Memaknai Keemerdekan Di Tengah Pandemi Covid-19 Di Desa Mentoso Kecamatan Jenu Kabupaten Tuban - Sulistyani Eka Lestari; Nur Aziz; Grahadi Purna Putra; Nuris Pratama Wisesa; Aguk Nugroho (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2021)
As a result of the Covid-19 pandemic, the Government of the Republic of Indonesia, both central and regional, is trying to make a policy that is set forth in a regulation or legislation needed to anticipate the spread of Covid-19 and prevent transmission of Covid-19 from one person to another by how to implement health protocols. For this reason, the public needs to know this and respond by complying with health protocols, because anyone who violates these health protocols will be subject to sanctions. Given the lack of awareness in the community about the importance of this matter, it is necessary to socialize and provide education to the community, especially residents of Mentoso Village, Jenu District, Tuban Regency to comply with health protocols, one of which is to wear a mask when leaving the house and understand the laws and regulations that have been made by the government, especially the regional government of Tuban district. There is an effort from the government is the use of vaccinations that are already running with all the regulations that support the prevention of the Covid-19 pandemic. The Covid-19 pandemic that we are facing together will further strengthen our commitment to social solidarity which has become a national tradition, namely the spirit of Gotong Royong. It is better for us to interpret Gotong Royong not as a magic spell, but rather as a call to care for others with a willingness to be empathetic and willing to dedicate ourselves and our possessions to help fellow citizens in need. In this sense, we may celebrate this independence with gratitude to God Almighty through compassion for our brothers and sisters who are survivors of Covid-19. This Community Service Activity (PPM) at the University of Sunan Bonang Tuban was attended in particular by 15 Mentoso villagers, the activity was held at the Mentoso Village Hall, Jenu District, Tuban Regency. carried out by socializing and/or providing education through the lecture method. The lecture method is used to explain the laws and regulations related to the implementation of health protocols and the importance of vaccination in Indonesia and specifically in Tuban Regency and the social agenda by distributing groceries to participants. Service activities as a whole can be said to be good and successful, seen from the success of the target number of training participants (100%), the achievement of training objectives (75%), the achievement of planned material targets (80%), and the participants' ability to master the material (75%).